TEST-RETEST RELIABILITY STROOP TASK BERBAHASA INDONESIA - Putri Nurazizah Rukman; Miqdad Daly Ahmad; Udi Rosida Hijrianti (Universitas Negeri Padang, 2025)
The stroop task is a method of measuring selective attention that demonstrates automatic and controlled cognitive processes. The stroop task as a digitalized measuring tool makes it easier for users to administer and score efficiently. However, this digital stroop task is not yet available in the Indonesian version. Meanwhile, the use of English has not been fully mastered by layers of Indonesian society, which causes the risk of less than optimal test results. This research is a non-experimental quantitative research which aims to test the psychometric properties using a test-retest approach at a time interval of 7 days on the Indonesian language Stroop task measuring instrument in early adult individuals with the criteria of being 18-25 years old and not color blind. The reliability test was analyzed using the ICC formula and strengthened with the Cronbach's alpha internal consistency test. The results of research conducted on 170 respondents using accidental sampling showed good ICC coefficient results (r = 0.87, 95% confidence interval (CI), 0.64, 0.93) and a Cronbach alpha coefficient of (α = 0.93). Thus, the stroop task in Indonesian has satisfactory psychometric properties and is suitable for use in the Indonesian population.